Essence-Temporality Paradigm: What the architecture of tobacco allows to glimpse - García Nofuentes, Juan Francisco; Martínez Ramos e Iruela, Roser (Estoa. Journal of the Faculty of Architecture and Urbanism, 2019)
The «tobacco curing houses» scattered across the landscape of the Vega of Granada, mean something more than the memory of a marginal, beautiful and forgotten architecture. These simple models of industrial architecture that pursue the «essence», turn into light and sensations sieves, that can be pierced by senses owing to a drilled and protagonist epidermis, with great expectations of giving shelter to the most unlike uses. From the inquiry into the infallibility of the architectural fact, coming from the observation of «permanent qualities», foreign to styles, uses, economy, social conditions or culture, which make architecture an eternal demand, the «invariants» that are being discovered from the inductive analysis of models of the embryonic architecture of this peculiar inherited heritage, are revealed, in a constant intertextual exercise.